Marketing management : cases for creative problem solving - Weinstein, Laurence Martin, 1944- (South-Western College, 2001)
This book is divided into seven parts: Overview of marketing, business ethics; Market positioning and segmentation; International marketing; Marketing research; Branding, New product development, and Packaging; Pricing and Distribution; and Promotion.